Harmonization of Consumer Protection in Dropshipping Transactions: Fiqh Muamalah and Positive Law Approaches to Defective E-Commerce Products - Ismiyatus Tsaniyah; Moh. Karim; Ahmad Musadad (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2026)
This research seeks to examine and align consumer protection in dropshipping practices through the perspectives of Islamic jurisprudence (fiqh muamalah) and Indonesian positive law, particularly concerning liability for defective products in electronic commerce. A qualitative method was applied using a combination of normative legal analysis and empirical inquiry. The normative approach reviews relevant regulations such as the Consumer Protection Law (UUPK No. 8/1999), the Electronic Information and Transactions Law (UU ITE), and fiqh muamalah principles including salam, wakalah, and samsarah contracts. Empirical data were obtained through semi-structured interviews with two dropshipping practitioners in Modung District, Bangkalan Regency. The results of the study show that the prevailing practice of dropshipping generally does not meet the principle of contract certainty in fiqh muamalah. From a positive law perspective, dropshippers are still positioned as sellers who are obliged to bear losses due to defects. Therefore, this study emphasizes the importance of formulating a harmonization model through the use of contracts that are explicitly in accordance with Islam, as well as affirming the legal responsibility of dropshippers. Thus, it is hoped that dropshipping practices can be declared valid under sharia law while reflecting the values of fairness, transparency, and consumer protection.